Mid-life social participation in people with intellectual disability: The 1958 British birth cohort study - Wang, Zuyu; Sommerlad, Andrew; Hassiotis, Angela; Richards, Marcus; Livingston, Gill (PloS one, 2024)
Low social participation is a potentially modifiable risk factor for cognitive deterioration in the general population and related to lower quality of life (QoL). We aimed to find out whether social participation is linked to cognitive deterioration and QoL for people with borderline intellectual functioning and mild intellectual disability. We used data from the National Child Development Study, consisting of people born during one week in 1958, to compare midlife social participation in people with mild intellectual disability, borderline intellectual functioning, and without intellectual impairment. We defined social participation as 1. confiding/emotional support from the closest person and social network contact frequency at age 44, and 2. confiding relationships with anyone at age 50. We then assessed the extent to which social participation mediated the association between childhood intellectual functioning and cognition and QoL at age 50. 14,094 participants completed cognitive tests at age 11. People with borderline intellectual functioning and mild intellectual disability had more social contact with relatives and confiding/emotional support from their closest person, but fewer social contacts with friends and confiding relationships with anyone than those without intellectual disability. Having a confiding relationship partially mediated the association at age 50 between IQ and cognition (6.4%) and QoL (27.4%) for people with borderline intellectual functioning. We found adults with intellectual disability have positive family relationships but fewer other relationships. Even at the age of 50, confiding relationships may protect cognition for people with borderline intellectual functioning and are important for QoL.